Characterization of Potassium Permanganate Treated Natural Fibers and Its Eco-Friendly Friction Composites - N. Jiyas; Indu Sasidharan; K. Bindu Kumar; P. Senthamaraikannan; R. Kumar (Journal of Natural Fibers)
This study explores the transformative effects of permanganate treatment on Pseudoxytenanthera stocksii (P. stocksii) bamboo fibers, benchmarking their enhanced properties against other natural fibers. P. stocksii fibers, enriched by a 15.5% increase in cellulosic content through permanganate treatment, exhibit remarkable improvements in material performance, including a 4% increase in density, 52% enhanced water absorption resistance, and significantly reduced moisture content. These fibers demonstrate exceptional thermal stability, achieving a maximum degradation temperature (Tmax) of 353.15°C, outclassing hemp fibers (Tmax 336.2°C). With a porosity of 7%, density of 1.19 g/cc, and hardness of 89 hRB, the treated fibers reinforced friction composites exhibit superior structural integrity. Tribological analysis further underscores their utility, with a coefficient of friction of 0.52, a specific wear rate of 1.87 × 10−5 mm3/Nm, and an impressive friction stability of 95%. These results position permanganate-treated P. stocksii bamboo fibers as a viable candidate for friction-assistive applications, paving the way for sustainable innovations in composite materials. The findings not only highlight the untapped potential of P. stocksii fibers in advancing green tribology but also underscore their broader implications for reducing environmental impact in engineering applications.